MODEL BIROKRASI INOVATIF DALAM PEMBANGUNAN IBU KOTA NUSANTARA: ANTARA HARAPAN DAN REALITAS PELAKSANAAN - Zaenal Abidin AS (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
The relocation of Indonesia’s national capital to Nusantara not only represents a large-scale infrastructure development project, but also reflects a fundamental transformation in the country’s governmental and bureaucratic governance system. The development of the Nusantara Capital City (IKN) serves as a significant momentum for the implementation of an innovative bureaucratic model through the establishment of the Nusantara Capital Authority (Otorita IKN) as a special institution endowed with broad administrative, fiscal, and planning powers. Unlike conventional bureaucracies, which tend to be hierarchical and procedural, the Nusantara Capital Authority is designed with a more flexible and collaborative structure to accelerate decision-making processes and strengthen cross-sectoral coordination. This study aims to analyze the implementation of an innovative bureaucratic model in the development of IKN by identifying innovative elements within institutional governance, the digitalization of public services, and multisectoral collaboration mechanisms. This research employs a descriptive qualitative approach through literature review and policy document analysis using a qualitative content analysis method. The study examines Law Number 3 of 2022 concerning the National Capital City, Presidential Regulation Number 63 of 2022, government reports, and contemporary public administration literature. The theoretical framework refers to the concepts of New Public Governance and innovative public governance, which emphasize institutional flexibility, collaborative governance, and governmental digitalization. The findings indicate that, normatively, the Nusantara Capital Authority has adopted the principles of innovative bureaucracy through the integration of digital systems, decentralization of decision-making, and the development of multisectoral partnerships. However, implementation in practice continues to encounter several challenges, including overlapping authority among institutions, weak cross-sectoral coordination, land governance issues, and limited participation of local communities and indigenous peoples in the development process. This study further reveals that institutional innovation has not been fully accompanied by transformation in organizational culture and bureaucratic capacity, resulting in a gap between policy design and implementation practices. The novelty of this research lies in its analysis of the relationship between the innovative bureaucratic design of the Nusantara Capital Authority and the practical realities of governance implementation in IKN development from a post-bureaucratic governance perspective. The findings affirm that the success of innovative bureaucracy depends not only on progressive institutional design, but also on regulatory harmonization, transformational leadership, bureaucratic capacity, and adaptive oversight mechanisms.